Creative negotiations - Romania-America 1920-1940 - ANDRAȘ, Sonia D.; MIHALY, Roxana (2024)
Throughout the interwar period, America’s interest in Romania grew and encompassed not only political, diplomatic, and historical aspects but also financial, cultural, and educational contributions. Thus, the Romanian- American ties throughout the interwar period suggest innate complexity and dynamism. This volume presents novel techniques and issues examined from an interdisciplinary, multi-perspective, and intercultural outlook. These approaches are derived from ideas such as discussion, negotiation, educational, and cultural communications.